1976
DOI: 10.1190/1.1440668
|View full text |Cite
|
Sign up to set email alerts
|

Vp/Vs—A POTENTIAL HYDROCARBON INDICATOR

Abstract: Theoretically and experimentally, the shear‐wave velocity of a porous rock has been shown to be less sensitive to fluid saturants than the compressional wave velocity. Thus, observation of the ratio of the seismic velocities for waves which traverse a changing or laterally varying zone of undersaturation or gas saturation could produce an observable anomaly which is independent of the regional variation in compressional wave velocity. One source of shear‐wave data in reflection seismic prospecting is mode conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

1985
1985
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(26 citation statements)
references
References 12 publications
0
24
0
2
Order By: Relevance
“…The ratio of the velocity of compressional waves, V p , to the velocity of shear waves, V^, is an important parameter for discriminating lithology and differentiating between water and gas saturations (Gregory, 1977;Tatham and Stoffa, 1976;Hamilton, 1979;Tatham, 1982). Recently, Rafavich et al (1984) suggested that VplV s velocity ratios discriminate mineralogy in limestones (specifically calcite vs. dolomite) and Wilkens et al (1984) showed that carbonate content dominates V p /V s in siliceous limestones.…”
Section: Vplv S Velocity Ratiomentioning
confidence: 99%
“…The ratio of the velocity of compressional waves, V p , to the velocity of shear waves, V^, is an important parameter for discriminating lithology and differentiating between water and gas saturations (Gregory, 1977;Tatham and Stoffa, 1976;Hamilton, 1979;Tatham, 1982). Recently, Rafavich et al (1984) suggested that VplV s velocity ratios discriminate mineralogy in limestones (specifically calcite vs. dolomite) and Wilkens et al (1984) showed that carbonate content dominates V p /V s in siliceous limestones.…”
Section: Vplv S Velocity Ratiomentioning
confidence: 99%
“…Stoffa (1976), andMcCormack et al (1984) demonstrated the combined use of V P and V S from seismic data for identification of hydrocarbon anomalies and stratigraphic interpretation. This was followed by development of empirical relationships between V P and V S in clastics (Castagna et al, 1985;Han et al, 1986) and carbonates (Rafavich et al, 1984).…”
Section: Geophysical Characterization Of Heavy-oil Formationsmentioning
confidence: 99%
“…To Figure 13.1a. PSSP reflections generated by conversion at the sea floor (after Tatham and Stoffa, 1976). (i) Geometry; (ii) the conversion coefficient versus angle of incidence in the water; the curves are labeled with the seafloor P-wave velocity in km/s.…”
Section: Solutionmentioning
confidence: 99%